2022
DOI: 10.1186/s12936-022-04303-6
|View full text |Cite
|
Sign up to set email alerts
|

The economic burden of malaria: a systematic review

Abstract: Background Quantifying disease costs is critical for policymakers to set priorities, allocate resources, select control and prevention strategies, and evaluate the cost-effectiveness of interventions. Although malaria carries a very large disease burden, the availability of comprehensive and comparable estimates of malaria costs across endemic countries is scarce. Methods A literature review to summarize methodologies utilized to estimate malaria t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 52 publications
0
35
0
Order By: Relevance
“…[42] This indicates that the direction of malaria risk depends on temperature, rainfall, and humidity. [42,43] Other studies [44,45] have also revealed that a reduction in malaria infections is associated with economic growth.…”
Section: Discussionmentioning
confidence: 99%
“…[42] This indicates that the direction of malaria risk depends on temperature, rainfall, and humidity. [42,43] Other studies [44,45] have also revealed that a reduction in malaria infections is associated with economic growth.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, many countries in Africa have a GDPPC well below the regional threshold ($2,250) for high malaria prevalence (Gallup and Sachs, 2000). Multiple studies have shown a strong correlation between high malaria burden and low GDPPC (Andrade et al, 2022), or low per capita income (Gallup and Sachs, 2000;Sarma et al, 2019). For example, the Sarma et al (2019) study found a 10% decrease in malaria incidence with an increase of 0.3% in average of income per capita.…”
Section: The Roles Of Socioeconomic and Demographic Factorsmentioning
confidence: 99%
“…Malaria imposes a significant economic and societal burden, which includes (i) direct healthcare costs associated with diagnosis and treatment, (ii) productivity fall translated to economic losses for individuals and communities, (iii) preventive measures carried out by governments, organizations, and individuals, (iv) research and development for new malaria treatments and improved diagnostic tools, and (v) tourism decrease in endemic areas. However, estimating the global malaria budget is challenging due to the lack of a standardized breakdown of expenses and a comprehensive, universally comparable quantification of the disease's economic impact on society and governments (Andrade et al, 2022). Nevertheless, it is worth mentioning that the total fund allocated to combat malaria through different initiatives has remained relatively stagnant since 2010, reaching only US$ 3.5 billion in 2021 (RBM Partnership to End Malaria, 2023; World Health Organization, 2022).…”
Section: Introductionmentioning
confidence: 99%